2020
DOI: 10.3889/oamjms.2020.4841
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Cervical Laminectomy and Fusion versus Cervical Laminoplasty Surgery in Degenerative Cervical Myelopathy: A Prospective Randomized Trial

Abstract: BACKGROUND: There is a lack of evidence of whether degenerative cervical myelopathy (DCM) is best treated through cervical laminoplasty (CLP) or cervical laminectomy with lateral mass fusion due to the lack of prospective randomized studies that are well designed. We conducted the largest prospective randomized trial to date to determine the comparative effectiveness and safety of both approaches. METHODS: In this prospective, randomized trial, we randomly assigned patients who had symptoms or signs of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…There was no significant difference in reported pain between groups at each post-op interval up to 24 months. The average improvement in overall pain was slightly greater in the LF group (1.8 points compared to 0.8 points for the LP group); however, this difference is likely attributed to a trend of greater baseline pain in the LF group, Other studies have seen a similar pattern of slightly greater pain improvement with LF in the setting of higher pain at baseline [16 , 17] . This phenomenon remains difficult to interpret due to the wide range of values of VAS score changes published by other comparison studies, varying between 0.2 and 4 points; in contrast, other studies observed greater pain improvement after LP [18] .…”
Section: Discussionmentioning
confidence: 75%
“…There was no significant difference in reported pain between groups at each post-op interval up to 24 months. The average improvement in overall pain was slightly greater in the LF group (1.8 points compared to 0.8 points for the LP group); however, this difference is likely attributed to a trend of greater baseline pain in the LF group, Other studies have seen a similar pattern of slightly greater pain improvement with LF in the setting of higher pain at baseline [16 , 17] . This phenomenon remains difficult to interpret due to the wide range of values of VAS score changes published by other comparison studies, varying between 0.2 and 4 points; in contrast, other studies observed greater pain improvement after LP [18] .…”
Section: Discussionmentioning
confidence: 75%